2011
DOI: 10.1371/annotation/45b44e2a-c751-418b-bbb7-7023998abdfc
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Identical Functional Organization of Nonpolytene and Polytene Chromosomes in Drosophila melanogaster

Abstract: Salivary gland polytene chromosomes demonstrate banding pattern, genetic meaning of which is an enigma for decades. Till now it is not known how to mark the band/interband borders on physical map of DNA and structures of polytene chromosomes are not characterized in molecular and genetic terms. It is not known either similar banding pattern exists in chromosomes of regular diploid mitotically dividing nonpolytene cells. Using the newly developed approach permitting to identify the interband material and locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…(5) Histone H1 dip localization in Kc cells [25]. (6) DNase I hypersensitivity sites (DHS) in S2 cells [27] and in salivary glands of third-instar larvae [22]. (7) Borders of the bands in the region, as defined by the 4HMM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) Histone H1 dip localization in Kc cells [25]. (6) DNase I hypersensitivity sites (DHS) in S2 cells [27] and in salivary glands of third-instar larvae [22]. (7) Borders of the bands in the region, as defined by the 4HMM.…”
Section: Discussionmentioning
confidence: 99%
“…Later it was shown that the DNA fragment affected by this deletion exhibits insulator properties. Namely, it can protect reporter transgenes from position effects and blocks enhancer-promoter communication [21].In different tissues, the proximal part of this DNA region has various DNase I-hypersensitive sites [21,22], whose presence is characteristic of many insulator elements [23,24]. Using whole genome data on the distribution of chromatin proteins and other characteristics of chromatin in D. melanogaster cell lines [25][26][27], areas enriched with dCTCF, Centorsomal protein 190 kD (CP190), and GAGA Factor (GAF) insulator proteins, as well as with open chromatin marks such as Chromator (CHRIZ) protein, RNA polymerase II, and chromatin remodeling proteins (ISWI, NURF301, dRING) were identified in the 5 region of the Notch gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, the polytene chromosomes, when available, can provide useful information about the correspondence of functional genome domains with the chromosome structure at the highest resolution. The organizational principles of polytene chromosomes, such as patterns of bands and interbands, have recently been likened to that of regular nonpolytene (interphase) chromosomes 18 . Therefore, the detailed physical mapping performed on high-pressure chromosome preparations has the potential to link DNA sequences to specific chromosomal structures such as bands, interbands, puffs, centromeres, telomeres, and heterochromatin; thus, creating chromosome-based genome assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning with C. Bridges, three types of structures were described in polytene chromosomes: interbands and two types of bands-large densely packed black bands and loose light ones that look grey under the light microscope [25][26][27]. In addition to morphology, the two types of bands differ in the degree of chromatin compaction level, replication time, gene density, the presence or absence of replication origins, the sets of proteins, histone modifications, and chromatin states (see below for details).…”
Section: Introductionmentioning
confidence: 99%
“…The development of molecular genetic methods of labeling P-element interband insertions helped to determine which types of proteins related to bands and interbands in general [27,[35][36][37]. The 4HMM mathematical model was developed using these data; it revealed four chromatin states that are distinguished by the presence of RNA polymerase II, Origin Recognition Complex (ORC), protein composition, and nucleosome modifications [38][39][40].…”
Section: Introductionmentioning
confidence: 99%